2017
DOI: 10.1177/2056305117693647
|View full text |Cite
|
Sign up to set email alerts
|

The Charlie Hebdo Attacks on Twitter: A Comparative Analysis of a Political Controversy in English and French

Abstract: In this article, we propose an original method combining large-scale network and lexicometric analysis to link identifiable communities of Twitter users with the main discursive themes they used in the aftermath of the Charlie Hebdo attacks in Paris, France in 2015. We used this method to compare tweets and user networks in French and in English. We observed that the majority of the users who tweeted about Charlie Hebdo were people without any particular affiliation, who were shocked by the attacks and immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 8 publications
2
22
0
5
Order By: Relevance
“…In this vein, prior works provide evidence that rumors could be rich in emotion words in order to appear sensational [20]. After all, it is common for people to express themselves through emotionally charged messages in an ambiguous situation surrounding the death hoax of a political figure [21]. Consistent with the literature, this paper confirms the affective nature of rumors.…”
Section: Resultssupporting
confidence: 85%
“…In this vein, prior works provide evidence that rumors could be rich in emotion words in order to appear sensational [20]. After all, it is common for people to express themselves through emotionally charged messages in an ambiguous situation surrounding the death hoax of a political figure [21]. Consistent with the literature, this paper confirms the affective nature of rumors.…”
Section: Resultssupporting
confidence: 85%
“…In spite of the popularity of the hashtags, discordant voices also appeared almost immediately after the attack, including hashtags expressing support for the bombers, such as #jesuisKouachi 1 (one of the terrorists), and many #jenesuispasCharlie hashtags (cf. Badouard 2015; de Lucena Ito 2015; An, Kwak, Mejova, Saenz De Oger, & Gomez Fortes 2016; Giglietto & Lee 2017; Smyrnaios & Ratinaud 2017). This latter group condemned the attacks but did not wish to use #jesuisCharlie for various reasons, mainly to express disagreement with the ideology of the Charlie Hebdo magazine, to criticize the Islam-related cartoons that Charlie Hebdo had published at an earlier date, or to oppose the political appropriation of the attacks by individuals and parties that had not previously identified with Charlie Hebdo and/or whose ideas were not in line with those of Charlie Hebdo (Badouard 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With recent terrorist attacks in Western European countries perpetrated by jihadists, the far right often frames these events as crises that represent insecurity in Europe on social media. It is true that terrorist attacks result in acute bursts of Twitter activity; exploring the publics discussing the attack on Charlie Hebdo, Smyrnaios and Ratinaud (2017) find that a small minority of users were active in an opportunity to criticize Muslims. Research has found that the far right amplifies existing Islamophobic frames that are well documented in newspapers (Törnberg and Törnberg 2016).…”
Section: Crisis Theme: Defence and Securitymentioning
confidence: 99%